African medicinal plants with anthelmintic properties against selected zoonotic helminths: a scoping review - Megnigueu, E. M.; Simsek, S.; Celik, F.; Kouam, S. F.; Ndjonka, D. (Paradigm Publishing Services-de Gruyter Brill Sp Zoo, 2025)
Zoonotic helminth infections remain a persistent public health challenge across Africa, causing considerable morbidity and economic losses in both humans and livestock. The emergence of anthelmintic resistance and limited access to conventional treatments have intensified interest in alternative therapeutic approaches. Medicinal plants, long used in traditional medicine, represent a promising source of bioactive compounds with potential anthelmintic activity. This scoping review examined the diversity, efficacy, and ethnopharmacological relevance of African medicinal plants traditionally used to treat helminthiasis, with a specific focus on Echinococcus granulosus, Taenia solium, and Fasciola hepatica. Following PRISMA guidelines, a systematic search of electronic databases identified 78 studies published between 2005 and May 2025, comprising 31 ethnobotanical surveys and 47 pharmacological investigations. Most studies focused on E. granulosus (n=19), followed by T. solium and F. hepatica (14 each). Ethnobotanical surveys reported 207 plant species from 54 families, while 57 species were evaluated pharmacologically. The most frequently studied families were Lamiaceae, Moringaceae, Euphorbiaceae, and Apocynaceae. Most studies relied on crude extracts, with few isolating or characterizing bioactive compounds. No clinical trials were reported, and methodological heterogeneity limited cross study comparability. Despite these limitations, several plant species demonstrated promising anthelmintic activity. This review highlights the underrepresented African contribution to ethnopharmacology and proposes future research directions, including bioassay-guided isolation, mechanistic studies, in vivo validation, and clinical evaluation. Integrating plant-based investigations within One Health strategies may provide affordable, accessible, and sustainable solutions for communities most affected by zoonotic helminths.
Keywords: African medicinal plants; zoonotic helminths; ethnopharmacology; anthelmintic